High‐Quality Ruddlesden–Popper Perovskite Films Based on In Situ Formed Organic Spacer Cations. Issue 41 (28th August 2019) - Qing, Jian; Kuang, Chaoyang; Wang, Heyong; Wang, Yuming; Liu, Xiao‐Ke; Bai, Sai; Li, Mingjie; Sum, Tze Chien; Hu, Zhangjun; Zhang, Wenjing; Gao, Feng
Abstract: Ruddlesden–Popper perovskites (RPPs), consisting of alternating organic spacer layers and inorganic layers, have emerged as a promising alternative to 3D perovskites for both photovoltaic and light‐emitting applications. The organic spacer layers provide a wide range of new possibilities to tune the properties and even provide new functionalities for RPPs. However, the preparation of state‐of‐the‐art RPPs requires organic ammonium halides as the starting materials, which need to be ex situ synthesized. A novel approach to prepare high‐quality RPP films through in situ formation of organic spacer cations from amines is presented. Compared with control devices fabricated from organic ammonium halides, this new approach results in similar (and even better) device performance for both solar cells and light‐emitting diodes. High‐quality RPP films are fabricated based on different types of amines, demonstrating the universality of the approach. This approach not only represents a new pathway to fabricate efficient devices based on RPPs, but also provides an effective method to screen new organic spacers with further improved performance. Abstract : A novel method is developed for fabricating high‐quality Ruddlesden–Popper perovskite films by directly using commercially available organic amines, avoiding extra chemical synthesis processing of organic ammonium halides. This new approach results in similar (and even better) device performance for both solar cells and light‐emitting diodes when compared with control devices fabricated from organic ammonium halides.